Electrochemical corrosion behavior of copper in graphene-based thermal fluid with different surfactants - Adeola O. Borode; Noor A. Ahmed; Peter A. Olubambi (Heliyon, 2021)
This study investigates the effect of different surfactant-dispersed graphene nanofluid on the electrochemical behavior of copper. This study was achieved by measuring the open circuit potential and potentiodynamic polarization of copper in the nanofluids at room temperature. The test media includes surfactant-free graphene nanofluid and graphene nanofluid dispersed using four different surfactants, which are sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, Gum Arabic, and Tween 80. The surface characterization and elemental composition of the copper sample before and after the corrosion tests were determined using a scanning electron microscope coupled with energy-dispersive X-ray spectroscopy. The phase formation after corrosion was also evaluated by measuring X-ray diffraction. The quantity of copper dissolved in the test media was evaluated using an inductively coupled plasma mass spectrometry (ICP-MS). The open-circuit potential measurements revealed that the current free corrosion potential of copper in the different surfactant-aided graphene nanofluids are different. The electrochemical corrosion potential, Tafel slopes, and corrosion rates revealed the better corrosion performance of copper in the nanofluid of different surfactants in the increasing order GA, SDS, Tween 80, and SDBS. Copper in GA-based graphene nanofluid was found to have the lowest corrosion rate while that of SDBS has the highest corrosion rate. However, the ICP-MS result revealed a discrepancy in the corrosion behavior and quantity of copper dissolved in the different test media. This could be attributed to the dissimilar dissolution-redeposition rate of copper in different media.